Average monthly coffee prices - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Whilst prices vary according to the variety of plant, the overall trend is a sharp fall in prices, with Robusta varieties falling the most. The composite price is an average of the averages.Producers of Colombian milds, 13% of all world output in...